A survey on content, layout and accessibility (CLA) of LAW083 MOOC among UiTM law foundation students / Mohd Safri Mohammed Na’aim ... [et al.] - Mohammed Naaim, Mohd Safri; Mohamad Hashim, Haswira Nor; Tumiran, Mohd Amzari; Akahsah, Namirah; Abdul Jamal, Jusniza; Abdullah, Farhah; Shaari @ Mat Saman, Nurulhasni; Amit, Siti Marina; Syed Hamid, Sharifah Shatrah (Penerbit UiTM (UiTM Press), 2025)
Massive Open Online Courses (MOOCs) are online learning environments designed for large numbers of participants and are typically free, open, and flexible. In 2019, Universiti Teknologi MARA (UiTM) launched UFUTURE, an online platform featuring UiTM MOOC among its integrated features. With the aim of improving learning quality, UiTM MOOC offers diverse learning materials and activities to accommodate students of various learning styles. Recognising its benefits, the Introduction to Law of Contract, Torts and Crimes (LAW083) course, a compulsory subject for law foundation students at the Centre of Foundation Studies, UiTM Selangor Branch, Dengkil Campus (COFS), was adapted into a MOOC. Although previous research has discussed students’ perceptions towards MOOC in learning various subjects, there has been no comprehensive study on law foundation students’ perceptions of using MOOC for learning LAW083 at COFS. This study employed a cross-sectional survey approach to collect primary data from UiTM Law Foundation students enrolled at COFS during Session 2 of the 2023/2024 semester. Based on Krejcie and Morgan’s (1970) formula, the sample size for the available population (N=720) was determined to be 251 after screening. The sampling method used for the respondents was purposive convenience sampling, where the online survey was distributed to the target population within the same academic session. This research acknowledges the limitation of sample size, which may affect the applicability of the findings concerning the LAW083 MOOC among UiTM Law Foundation students. Based on the results of the Friedman test that was conducted, the results presented the ranks of three (3) measures: content (C), layout (L), and accessibility (A), or CLA, which were found to be significantly different. The questionnaire assessed students’ opinions on the LAW083 MOOC regarding content, layout, and accessibility while also gathering feedback for improvements in these areas. The survey findings will be used to improve the CLA of the LAW083 MOOC. It is recommended for future studies to broaden the sample size and incorporate other qualitative methods such as interviews or focus group discussions to obtain more indepth insights.